The public awareness towards Islamic micro finance in Kuala Lumpur, Malaysia / Norhayati Mamat @ Ali - Mamat @ Ali, Norhayati (Faculty of Business and Management, 2013)
At a glance, the Islamic Microfinance (IMF) is getting appreciation by the whole world and everybody is utilizing it since it provides end-to-end solutions which that is not only about faith but encompasses a complete way of life. However, are we really aware about the IMF? How far that we know about the IMF? Which individuals should be afforded society’s protections? It is too good to be truth that the public should be aware of the IMF as it serves the whole society and offers many benefits to both Muslims and non-Muslim’s regardless religious beliefs as the IMF is a faith-based financial system which a mixture of three basic principles; economic, social and religious principles (Micro banker Connection, 2012). In response to these, this research paper attempt to determine the level of public awareness towards IMF in Kuala Lumpur, Malaysia. A survey method involves in this research study is by using a sample of 100 respondents taken from the Kuala Lumpur, Malaysia area. Based on the findings, it has been found that the normality test for all variables are normally distributed considered as parametric statistic which further proceed with Pearson Correlation test that shows positive and relatively strong relationship knowledge and the public awareness while moderate relationship for both government encouragements and social concerns with the significant value 1-tailed;0.000.The Cronbach’s Alpha values indicate all the variables are good range which is reliable and acceptable with highest Cronbach’s Alpha for independent variables is knowledge ; 0.894. The lowest average mean is knowledge; 2.8880 while the highest is social concerns; 3.6600 which indicates all the respondents gave the answers in range of2 (disagree) to 4 (agree) for all variable’s sections. Thus, all the results are attempted to reveal and answer all the research questions for this study.